Clustering Slope Stability from Using Drone, DEM Lineament Extraction And Rock Mass Rating In Pangkalan Koto Baru, West Sumatra, Indonesia - Tiggi Choanji; Yuniarti Yuskar; Dewandra BE Putra; Catur Cahyaningsih; Winanda Sakti (Journal of Applied Geospatial Information, 2018)
Clustering slope stability in the Pangkalan Koto Baru, West Sumatra has become one of priority in disaster management. The method used for this study are using the combination of structural lineament analysis, scanline with window sampling and Rock mass rating (RMR) calculations. The analysis results of the fourteen observed slope sites showed significant outcome, which seen in the structural lineament show dominant trend from northwest-southeast, which also correlate from the measurement of discontinuity by using scanline with window sampling. From RMR calculation, value showed range between 17 - 42 which belonged to class V (Very Poor Rock) - class III (Medium Rock ). Integration data of structural lineament, scanline method and RMR analysis suggested that 1 slope included in the very poor rock category, 12 slopes are poor rock category, and 1 slope in the medium rock category. So, it can be ascertained that most of the slopes will potentially be prone to landslides. Keywords: Slope Stability, RMR, Structural Lineament, Pangkalan Koto Baru, West Sumatra.